Accurate adjustment of feed formulation for broiler chickens on performance and lipid composition of meat - Pinto, Marcos Franke [UNESP]; Ferreira, Gabriela Silva [UNESP]; Garcia Neto, Manoel [UNESP]; Ponsano, Elisa Helena Giglio [UNESP]; Gonçalves, Camila Angélica [UNESP]; Bossolani, Iderlipes Luiz Carvalho [UNESP] (My University, 2014)
Most consumers consider the fat of chicken meat undesirable for a healthy diet, due to the high levels of saturated fatty acids and cholesterol. The purpose of this experiment was to investigate the influence of changes in dietary metabolizable energy level, associated with a proportional nutrient density variation, on broiler chickens performance and on the lipid composition of meat. Males and females Cobb 500 broilers were evaluated separately. Performance evaluation followed a completely randomized design with factorial 6x3 arrangement - six energy levels (2,800, 2,900, 3,000, 3,100, 3,200 and 3,300 kcal/kg) and three slaughter ages (42, 49 and 56 days). Response surface methodology was used to establish a mathematical model to explain live weight, feed intake and feed conversion behavior. Total lipids and cholesterol were determined in skinned breast meat and in thigh meat, with and without skin. For lipid composition analysis, a 3x3x2 factorial arrangement in a completely randomized design - three ration’s metabolizable energy levels (2,800, 3,000 and 3,300 kcal/kg), three slaughter ages (42, 49 and 56 days) and two sexes - was used. The reduction in the diet metabolizable energy up to close to 3,000 kcal/kg did not affect live weight but, below this value, the live weight decreased. Feed intake was lower when the dietary energy level was higher. Feed conversion was favored in a direct proportion to the increase of the energy level of the diet. The performance of all birds was within the range considered appropriate for the lineage. Breast meat had less total lipids and cholesterol than thigh meat. Thigh with skin had more than the double of total lipids of skinned thigh, but the cholesterol content did not differ with the removal of the skin, suggesting that cholesterol content is not associated with the subcutaneous fat. Intramuscular fat content was lower in the meat from birds fed diets with lower energy level. These results may help to define the most appropriate nutritional management. Despite the decrease in bird’s productive performance, the restriction of energy in broiler chickens feed may be a viable alternative, if the consumers are willing to pay more for meat with less fat.
Keywords: Meat fat; Cholesterol; Subcutaneous fat; Intramuscular fat; Healthy diet